Hemodynamic response in one session of strength exercise with and without electrostimulation in heart failure patients: a randomized controlled trial - Carvalho, Vitor Oliveira; Roque, Jean Marcelo; Bocchi, Edimar Alcídes; Ciolac, Emmanuel Gomes [UNESP]; Guimarães, Guilherme Veiga (My University, 2011)
Background: Studies have investigated the influence of neuromuscular electrostimulation on the exercise/muscle capacity of patients with heart failure (HF), but the hemodynamic overload has never been investigated. The aim of our study was to evaluate the heart rate (HR), systolic and diastolic blood pressures in one session of strength exercises with and without neuromuscular electrostimulation (quadriceps) in HF patients and in healthy subjects. Methods: Ten (50% male) HF patients and healthy subjects performed three sets of eight repetitions with and without neuromuscular electrostimulation randomly, with one week between sessions. Throughout, electromyography was performed to guarantee the electrostimulation was effective. The hemodynamic variables were measured at rest, again immediately after the end of each set of exercises, and during the recovery period. Results: Systolic and diastolic blood pressures did not change during each set of exercises among either the HF patients or the controls. Without electrostimulation: among the controls, the HR corresponding to the first (85 ± 13 bpm, p = 0.002), second (84 ± 10 bpm, p < 0.001), third (89 ± 17, p < 0.001) sets and recuperation (83 ± 16 bpm, p = 0.012) were different compared to the resting HR (77 bpm). Moreover, the recuperation was different to the third set (0.018). Among HF patients, the HR corresponding to the first (84 ± 9 bpm, p = 0.041) and third (84 ± 10 bpm, p = 0.036) sets were different compared to the resting HR (80 ± 7 bpm), but this increase of 4 bpm is clinically irrelevant to HF. With electrostimulation: among the controls, the HR corresponding to the third set (84 ± 9 bpm) was different compared to the resting HR (80 ± 7 bmp, p = 0.016). Among HF patients, there were no statistical differences between the sets. The procedure was well tolerated and no subjects reported muscle pain after 24 hours. Conclusions: One session of strength exercises with and without neuromuscular electrostimulation does not promote a hemodynamic overload in HF patients. (Cardiol J 2011; 18, 1: 39-46)
Keywords: Strength exercise; Cardiac rehabilitation; Electrostimulation; Hemodynamic response